Impact Of Entrepreneurial Skills And Family Occupation On Entrepreneurial Intentions - Muhammad Shoaib, Farooq; Norizan, Jaafar; Kartinah, Ayupp; Maimoona, Salam; Yasir Hayat, Mughal (Publications International Lahore, 2016)
This study is based on Ajzen’s theory of planned behavior; it is an attempt to identify the role of entrepreneurial skills on the individuals’ intention to choose self-employment, instead of looking for an organizational employment. Theory of planned behavior has remained often braced in the pitch of entrepreneurship. Though, very petite is yet to known about the role of personal entrepreneurial skills and entrepreneurial intention. Aim of this study is to get an insight of the existence and reach of the effects of entrepreneurial skills on the entrepreneurial intentions. To explore in the deep avenues of entrepreneurial intention an empirical analysis is conducted on a sample of 205 fresh graduates. Researcher used the structural equation modelling to test the hypothesis of this study. Findings of the study generally confirmed previous studies, since Entrepreneurial skills play a substantial role in entrepreneurial intention. Further implication may be devised in several more areas, especially for entrepreneurial education.